Proceedings IEEE INFOCOM 2006. 25TH IEEE International Conference on Computer Communications 2006
DOI: 10.1109/infocom.2006.100
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Fast and Robust Worm Detection Algorithm

Abstract: Abstract-Fast spreading worms are a reality, as amply demonstrated by worms such as Slammer, which reached its peak propagation in a matter of minutes. With these kinds of fast spreading worms, the traditional approach of signature-based detection is no longer sufficient. Specifically, these worms can infect all vulnerable hosts well before a signature is available. To counter them, we must devise fast detection algorithms that can detect new worms without signatures as they first begin to appear. We present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Bu et al suggested a worm detection scheme [17] based on the extraction of the alteration of arrival unsolicited scan rates in the early stage of worm propagation. Their work suggested a novel signal indicating the outbreak of an Internet worm, but this approach suffers from the problem of too many potential sources for false positive rate.…”
Section: Related Workmentioning
confidence: 99%
“…Bu et al suggested a worm detection scheme [17] based on the extraction of the alteration of arrival unsolicited scan rates in the early stage of worm propagation. Their work suggested a novel signal indicating the outbreak of an Internet worm, but this approach suffers from the problem of too many potential sources for false positive rate.…”
Section: Related Workmentioning
confidence: 99%
“…Internet worm tomography, however, cannot be translated into the linear inverse problem due to the complexity of epidemic spreading, and therefore presents new challenges. Several statistical detection and estimation techniques have been applied to Internet worm tomography, such as maximum likelihood estimation (39), Kalman filter estimation (48), and change-point detection (2). Figure 6 further illustrates an example of Internet worm tomography on estimating when a host gets infected, i.e., the host infection time, from our previous work (39).…”
Section: Destination Detection and Defensesmentioning
confidence: 99%
“…For example, in modern high speed networks, data traffic in the form of packets can arrive at the network link in the speed of gigabits per second, creating a massive data stream. A sequence of packets between the same pair of source and destination hosts and their application protocols form a flow, and the number of distinct network flows is an important monitoring metric for network health (for example, the early stage of worm attack often results a significant increase in the number of network flows as infected machines randomly scan others, see Bu et al (2006)). As another example, it is often useful to monitor connectivity patterns among network hosts and count the number of distinct peers that each host is communicating with over time (Karasaridis et al, 2007), in order to analyze the presence of peer-to-peer networks that are used for file sharing (e.g.…”
Section: Introductionmentioning
confidence: 99%